Squamous cell esophageal cancer in patient with Barret's esophagus: case report - Gomes, Fábio da Silva (2005)
The squamous cell esophageal cancer is the most common neoplasia of the esophagus, and the main risk factors known are alchool and tobacco use. In the developed countries, the incidence of adenocarcinoma of the esophagus had been increased, and it association with Barret's esophagus is well established. In this report, we present the case of a patient with Barret's esophagus and the diagnosis of squamos cell esophageal cancer associated with intestinal metaplasia. This very rare association has few reports in the literature. The authors report the case and review the index publications of similar cases.